THE RECEPTION OF UKRAINIAN EMIGRATION LITERATURE ON THE PAGES OF THE JOURNAL „SUCHASNIST” - Бандура , Георгій (Кафедра полоністики Навчально-наукового інституту філології Київського національного університету імені Тараса Шевченка, 2022)
The article reviews the publications of literary journal “Suchasnist” devoted to emigration literature. The article by G. Grabovich “Great Literature”, in which the author analyzed the course of the famous discussion on the Art Ukrainian movement period, and the meaning of the idea of “Great literature” that had formed its antithesis – the New York group of poets. One of the most significant publications of “Suchasnist” was the report entitled “From the Chronicle of Literary Life in the Diaspora” by G. Kostiuk, the Head of the Ukrainian Writers Assosiation “Slovo”. The first part was about organizational activity of the association, and the second – about creative achievements of writers, paying attention to the “ideological and artistic essence” of the analyzed works. It is noted that the journal published a variety of materials devoted to the development of emigration poetry: interviews, reviews, articles on the works of the New York young poets group, as well as the recognized masters V. Barka, Yuri Klen, E. Malaniuk, and others. Besides the poetry, the constant focus of the journal was the prose. The reviews by A.G. Gorbach considered historical novels and the stories by M. Lazorsky, Y. Radzikevic, P. Fedenko, written from the standpoint of Ukrainian historical science, as an alternative to the Ukrainian Soviet-style literature based on Russian / Soviet historiography. Journal's editorial team paid also much attention to the works interpreting the fate of the Ukrainians during the twentieth century. Numerous publications examined in particular the works of little-known prose writers (E. Zagachevsky), not yet properly appreciated ones (O. Izarsky), as well as internationally recognized ones (I. Bagryany, V. Barka). A number of review articles devoted to the work of different prose writers, such as L. Zaleska-Onyshkevich, O. Tarnavsky, Y. Stefanyk, belongs to the type of literary portraits or scientific critical essays the “mainland” reader got used to. The journal publications have often enjoyed a significant resonance. These include materials intended to remind emigration of the life and work of V. Vynnychenko: articles by M. Molnar and G. Kostyuk, Gusar-Struk and I. Lisyak-Rudnytsky.

У статті зроблено огляд публікацій журналу «Сучасність», присвячених еміграційному письменству. Відзначено, що журнал друкував різножанрові матеріали – статті, рецензії, інтерв’ю, в яких розглядався тенденції розвитку поезії (доробок як молодих поетів нью-йоркської групи, так і визнаних метрів В. Барки, Юрія Клена, Є. Маланюка та ін.), аналізувалася історична белетристика М. Лазорського, Ю. Радзикевича, П. Феденка, твори, у яких осмислювалася доля української людини впродовж ХХ ст., що належали перу письменників і малознаних (Є. Загачевський), і ще належно не поцінованих (О. Ізарський), і загальновизнаних (І. Багряний, В. Барка). До типу звичних для «материкового» читача літературних портретів або науково-критичних нарисів автор зараховує низку оглядових статей, присвячених творчості того чи іншого прозаїка, зокрема статті Л. Залеської-Онишкевич, О. Тарнавського, Ю.Стефаника. Не раз уміщені в журналі публікації мали значний резонанс. До них слід віднести матеріали, покликані нагадати еміграції про життя і творчість В. Винниченка: статті М. Мольнара і Г. Костюка, Гусара-Струка і І. Лисяка-Рудницького.
РЕЦЕПЦІЯ УКРАЇНСЬКОЇ ЕМІГРАЦІЙНОЇ ЛІТЕРАТУРИ НА СТОРІНКАХ ЖУРНАЛУ «СУЧАСНІСТЬ»
Keywords: emigration; literary process; journal; genre; article; review; interview; еміграція; літературний процес; журнал; жанр; стаття; рецензія; інтерв’ю